The Effect of Thymoquinone on Progressive Brain Damage: An Experimental Study in a Wistar Rat Model of Intracerebral Hemorrhage - Thohari, Khamim; Fauzi, Asra Al; Purwanto, Djoko Agus (Borneo Journal of Pharmacy, 2026)
Intracerebral hemorrhage (ICH) accounts for 20% of stroke cases and is associated with a 40–50% mortality rate, yet effective neuroprotective therapies remain lacking. This study evaluated the therapeutic efficacy and molecular mechanisms of thymoquinone (TQ), the primary bioactive constituent of Nigella sativa, in a Wistar rat model of ICH. Male Wistar rats (n = 55, 200–220 g) were randomized into five groups: untreated control, untreated ICH, vehicle-treated ICH (corn oil for 7 days), and ICH treated orally with TQ at 150 mg/kg or 250 mg/kg body weight daily for 7 days. ICH was induced via autologous blood injection (0.12 mL) into the brain parenchyma. Biomarkers for neuroinflammation (NLRP3, TNF-α, IL-6, IL-1β), oxidative stress (SOD, MDA), tissue remodeling (MMP-9), and neuronal necrosis were quantified using ELISA, immunohistochemistry, and histological staining. TQ administration significantly elevated MMP-9 levels (p = 0.000) compared with untreated ICH controls and markedly suppressed NLRP3, TNF-α, and IL-1β expression. Furthermore, TQ increased SOD antioxidant activity, whereas MDA levels remained elevated. These neuroprotective effects were dose-dependent, with maximal modulation observed at 250 mg/kg TQ. In conclusion, TQ modulates critical inflammatory and oxidative pathways in experimental ICH while unexpectedly upregulating MMP-9, suggesting a complex dual function in early neuroprotection and subsequent tissue remodeling. These findings demonstrate that TQ holds promising potential as a natural neuroprotective agent for hemorrhagic stroke management.